Determinants of Female Genital Cutting Practices Among Girls Aged 0–6 Years in Kayamanya Village, Indonesia - Longgupa, Lisda Widianti; Ramadhan, Kadar; Nurfatimah, Nurfatimah; Kasmawati, Kasmawati (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Background: Female Genital Cutting (FGC) remains a deeply embedded cultural practice in several regions of Indonesia despite regulatory prohibitions. The practice poses significant risks to the health, rights, and well-being of young girls. This study aimed to describe the determinants of FGC practices among mothers of girls aged 0–6 years in Kayamanya Village, Central Sulawesi. Methods: This descriptive study involved 87 mothers selected using simple random sampling. Data were collected using a validated structured questionnaire assessing knowledge, attitudes, sociocultural support, and family support. Descriptive statistics were used to present the distribution of all variables. Results: The prevalence of FGC was 81.6%. Most mothers were aged 20–35 years (76%), had a high school education (47%), and were unemployed (79%). Family support (65.5%) and sociocultural influence (50.6%) were the most prominent determinants sustaining the practice. Maternal knowledge remained low, with 62% showing poor understanding of FGC-related risks. Conclusion: FGC remains highly prevalent in Kayamanya Village and is strongly sustained by family and sociocultural pressures. Culturally sensitive community-based interventions are needed to improve knowledge and address misconceptions surrounding FGC.